Influences of persistent overweight on perceptual-motor proficiency of primary school children: the North-West CHILD longitudinal study - Elna de Waal; Anita Elizabeth Pienaar (BMC, 2021)
Abstract Background Overweight can be a precursor of poor motor execution, negatively impacting the overall development of school-aged children on various levels. This study determined the long-term influences of overweight on perceptual-motor proficiency (PMP) of primary school children in the North-West Province of South Africa. Methods The study, which included 381 participants, formed part of the NW-CHILD longitudinal study from Grade 1 (6.86 years, ± 0.39) in 2010 to Grade 7 (12.9 years, ± 0.38) in 2016. Socioeconomic categories, called quintiles, were used to compare high and low socioeconomic status groups. Overweight was identified when BMI values fell above the 85th percentile, using age- and gender-specific cut-off points. The group was categorised into 4 BMI groups (never overweight, persistent overweight, overweight-to-normal and normal-to-overweight). The Bruininks Oseretsky Test of Motor Proficiency-2 (BOT-2) Short Form and selected composites measuring strength, balance, and running speed and agility were used to assess PMP. Results A repeated measures ANOVA analysis indicated specific PMP differences between different BMI groups, but not total motor proficiency (BOT-2 Short Form total) differences. Practical significant group differences (Cohen's d-values) were found in running speed and agility, strength, balance and the BOT-2 total, over seven primary school years. The persistent overweight group showed the poorest performance over time, but also showed deteriorating skills and a gradual widening in perceptual-motor skills performance, compared to the other groups. BMI-related differences in perceptual-motor coordination were also more pronounced in older age groups. Conclusions Persistent overweight negatively impacts specific motor-proficiency components, while improving weight status can counter these effects, which highlights the importance of timeous intervention to combat obesity at a young age.